2007
DOI: 10.1038/nature05661
|View full text |Cite
|
Sign up to set email alerts
|

Melanoma biology and new targeted therapy

Abstract: Melanoma is a cancer that arises from melanocytes, specialized pigmented cells that are found predominantly in the skin. The incidence of melanoma is rising steadily in western populations--the number of cases worldwide has doubled in the past 20 years. In its early stages malignant melanoma can be cured by surgical resection, but once it has progressed to the metastatic stage it is extremely difficult to treat and does not respond to current therapies. Recent discoveries in cell signalling have provided great… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
1,088
0
36

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 1,203 publications
(1,137 citation statements)
references
References 85 publications
13
1,088
0
36
Order By: Relevance
“…Recent findings indicate that MITF is an oncogene and also has a role in melanoma development 3 . The biological functions of MITF in melanoma cells are likely to be determined at least in part by alterations in its protein level: high MITF protein levels are anti-proliferative and suppress melanoma cell invasion; medium levels are pro-proliferative; and low levels are required for melanoma-cell invasion 20 . In this study, we have identified the deubiquitination of MITF as a potent mechanism that regulates MITF protein turnover.…”
Section: Discussionmentioning
confidence: 99%
“…Recent findings indicate that MITF is an oncogene and also has a role in melanoma development 3 . The biological functions of MITF in melanoma cells are likely to be determined at least in part by alterations in its protein level: high MITF protein levels are anti-proliferative and suppress melanoma cell invasion; medium levels are pro-proliferative; and low levels are required for melanoma-cell invasion 20 . In this study, we have identified the deubiquitination of MITF as a potent mechanism that regulates MITF protein turnover.…”
Section: Discussionmentioning
confidence: 99%
“…and RAS pathway genes [42]) is characteristic for basal-type breast cancers. Comparable gene mutation profiles among basal-type breast cancers and melanomas, and likely also pancreatic cancers [43], might be conceivable given the typically aggressive clinical course of these tumor types and their frequent inherent therapy resistance.…”
Section: Gene Mutation Profiles Provide a Genetic Basis For Luminal-tmentioning
confidence: 99%
“…Whilst melanoma skin cancer occurs worldwide at a rate of 132,000 cases each year [1], non-melanoma skin cancer makes up the majority of recorded cases with between 2 to 3 million cases diagnosed each year (www.who.int).…”
Section: Introductionmentioning
confidence: 99%